Plasma-assisted toxic agent self-degradation composite protection material and preparation method thereof

By using plasma assisted technology to grow active components on the surface of protective clothing materials, the problem of traditional protective clothing materials blocking heat dissipation is solved, and the interception and conversion of toxic chemicals is achieved, and the comprehensive functions of protection, degradation and moisture permeability are achieved.

CN119505331APending Publication Date: 2025-02-25HUBEI HUAQIANG HIGH TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541827.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional protective clothing materials block heat dissipation, causing wearers to face risks such as dehydration and fainting, and the protection methods of existing materials have secondary pollution and insufficient logistical cleaning.

Method used

Plasma assisted technology is used to grow active components in situ on the surface of the substrate material to form a plasma activation layer, and the active substances such as zirconium-based metal organic framework (such as MOF808, UiO-66-NH2) are loaded through ultrasonic mixing and continuous folding methods to realize the adsorption and catalytic degradation functions of poisonous agents.

Benefits of technology

It realizes the interception and conversion of toxic chemicals into non-toxic substances, has comprehensive functions of protection, degradation and moisture permeability, and improves the physiological comfort and environmental friendliness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505331A_ABST
    Figure CN119505331A_ABST
Patent Text Reader

Abstract

The invention discloses a plasma-assisted toxic agent self-degradation composite protection material and a preparation method thereof, and belongs to the field of chemical protection. The composite protective material comprises a substrate material and an active component growing in situ on the surface of the substrate material based on plasma treatment. The material is high in surface active component loading rate, simple in preparation process and beneficial to batch production, provides a new thought for improving the comprehensive protection level in the chemical protection field, and is wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical protection, and in particular to a plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof. Background Art

[0002] With the increasing demand for protective equipment protection in my country. Traditional protective clothing is generally made of highly insulating materials such as butyl rubber and halogenated butyl rubber. These materials have demonstrated excellent ability to completely block the penetration of various vapors and liquids, ensuring that the wearer is protected from harmful external substances. However, this advantage is also accompanied by significant disadvantages, namely, it cuts off the water vapor transmission path, making it difficult for the wearer's body heat to dissipate, which in turn causes heat accumulation problems. Wearing such protective clothing for a long time may put the wearer at risk of dehydration and fainting, and even in the most serious cases, may threaten life safety. On the other hand, the existing protective materials resist by physical adsorption or isolation, which has deficiencies such as secondary pollution and logistics decontamination.

[0003] At present, porous adsorption or catalytically active materials have been applied to the rapid catalysis of poisons and their simulants. They usually have high porosity, ultra-high specific surface area, rich chemical composition and catalytic active sites. However, the integration of active materials and substrate materials is still a difficult problem to be solved. For example, adding active substances to the substrate material system through blending will destroy its basic structure and affect mechanical properties such as breaking strength and elongation; the direct loading method using the in-situ growth method is not ideal, because the membrane material is mostly composed of an inert polymer main chain and lacks active sites on the surface.

[0004] Therefore, it is necessary to provide solutions for the physiological comfort of materials and their low-toxicity transformation. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a composite material which is physiologically comfortable and has both protective and disinfection functions and a preparation method thereof.

[0006] In order to solve the above problems, the present invention provides a plasma-assisted composite protective material for self-degradation of toxic agents, comprising: The inner layer substrate material has selective permeability, including polyvinylidene fluoride quaternary ammonium membrane material, polyvinylidene fluoride sulfonic acid membrane material, sulfonated polyphenylene ether membrane material, etc.; The active components grown in situ on the surface of the substrate material based on plasma treatment have the function of adsorbing toxic agents and catalytic degradation, including zirconium-based metal organic frameworks (such as MOF808, UiO-66-NH2), Zr(OH)4, etc.

[0007] The preparation method of a plasma-assisted composite protective material for self-degradation of toxic agents of the present invention is as follows: Step 1: Plasma treatment. Use an air atmosphere / nitrogen / oxygen plasma excitation device to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, and set the discharge voltage, frequency, working distance and other parameters. After a period of plasma discharge, a plasma activation layer is formed on the film surface.

[0008] Step 2: prepare the precursor solution and mix it by ultrasonic to make it evenly dispersed.

[0009] Step three, in-situ loading. Through the continuous folding method, the base material forming the surface activation layer is immersed in the precursor solution, the immersion temperature is 25°C, and the immersion time is 5 minutes. After taking it out, place it in an oven at 80°C to 140°C to allow the reaction to proceed for 12h to 24h. The reaction process is carried out in a closed environment, such as the reaction under high pressure and temperature conditions in a polytetrafluoroethylene reactor well known to those skilled in the art. After the reaction is completed, cool to room temperature, take out the membrane, rinse it three times, and vacuum dry it to obtain a composite protective material with active components loaded on the surface.

[0010] As a further improvement of the present invention, in step 1, the reaction gas is air, nitrogen or oxygen, the discharge voltage is 30-50 kV, the frequency is >40 kHz, the working distance is 3-5 cm, and the discharge time is 5-10 min. In some preferred embodiments, the frequency is in the range of 50-100 kHz.

[0011] As a further improvement of the present invention, in step 2, the precursor solution can be a mixture of zirconium oxychloride octahydrate, trimesic acid, glacial acetic acid and deionized water, the molar ratio of zirconium oxychloride octahydrate and trimesic acid is 0.8-3, and the volume ratio of glacial acetic acid and deionized water is 0.2-0.8.

[0012] As a further improvement of the present invention, in step 2, the precursor solution can be a mixture of zirconium oxychloride octahydrate, trimesic acid, trifluoroacetic acid and deionized water, the molar ratio of zirconium oxychloride octahydrate and trimesic acid is 0.8-3, and the volume ratio of trifluoroacetic acid and deionized water is 0.2-0.8.

[0013] As a further improvement of the present invention, in step 2, the precursor solution can be a mixture of zirconium tetrachloride, 2-aminoterephthalic acid and acetone, and the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 0.8 to 1.2.

[0014] As a further improvement of the present invention, in step 2, the precursor solution can be a mixture of zirconium tetrachloride, terephthalic acid, acetic acid and N,N-dimethylformamide (DMF), the molar ratio of zirconium tetrachloride and terephthalic acid is 0.2-0.5, and the volume ratio of acetic acid and N,N-dimethylformamide is 0.01-0.2.

[0015] As a further improvement of the present invention, after the membrane material is reacted, rinsed and vacuum dried in the precursor solution, it needs to be immersed in a NaOH solution at room temperature for 1-2 hours, and the concentration of the NaOH solution is 10-20%. Finally, it is centrifugally washed with DMF and ethanol to obtain the final product.

[0016] As a further improvement of the present invention, in step three, the solvent used to rinse the membrane three times can be any one or two of deionized water, methanol, DMF, and ethanol.

[0017] Beneficial effects of the present invention: 1. The plasma-assisted composite protective material for self-disinfection of toxic agents of the present invention can intercept toxic chemical substances and utilize the active components originally grown on the surface of the material to convert them into non-toxic substances. It is a material that integrates protection, degradation and moisture permeability.

[0018] 2. The plasma-assisted preparation method of the composite protective material for self-disinfection of toxic agents of the present invention adopts a plasma treatment method with a significant surface modification effect, and -NH2, -OH and -COOH can all be successfully loaded onto the surface of the membrane material, providing reaction sites for the efficient loading of active components. It has the characteristics of high efficiency, environmental friendliness, flexibility and controllability, and has broad application prospects.

[0019] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following specifically cites a preferred embodiment and describes it in detail with the accompanying drawings as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Attached Figure 1 This is an electron microscope image of the surface of the MOF808@polyvinylidene fluoride quaternary ammonium membrane obtained in Example 1. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0022] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0023] The following are the characterization test methods for materials: The selective permeability of composite protective materials is mainly determined by examining the moisture permeability and protective performance of the materials. Refer to GB / T 12704.2-2009 for moisture permeability test. Refer to GJB 3253-98 for the amyl sulfide "liquid-gas" protection time test of composite protective materials. Fix the composite protective material with oil-proof fabric and chloramine-Congo red indicator paper on the No. 6 instrument, drop 40 mg of amyl sulfide liquid on the surface of the composite protective material covered with oil-proof fabric, start timing, stop timing and record the time when the test paper turns blue, and use this time as the end point of the material's "liquid-gas" protection time.

[0024] The prepared composite protective material was tested for breaking strength according to GB / T 528-2009.

[0025] The prepared composite protective material was reacted with dichloroethyl ethyl sulfide (2-CEES) to test its degradation ability. According to the GJB 3638A-2020 method, 2-CEES was accurately measured with a micro syringe and evenly dropped on the surface of the material to form a 5g / cm 2 The initial density of 2-CEES. After a period of time, dichloromethane was used to extract the remaining 2-CEES, and the gas chromatography-sulfur phosphorus detector (GC-FPD) was used for analysis. Detection conditions: The chromatographic column is a quartz capillary column with a stationary phase of 14% cyanopropylphenyl / 86% dimethylpolysiloxane, with a length of 30m, an inner diameter of 0.25mm, and a film thickness of 0.25μm. The injection port temperature is 250℃, the detector temperature is 260℃, the initial column temperature is 60℃, maintained for 1min, and the temperature is increased to 250℃ at a rate of 15℃ / min and maintained for 2min. The non-split injection mode is adopted, the non-split time is 0.7min, and the injection volume is 1.0μL.

[0026] Example 1 A plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof, comprising the following steps: Step 1: Plasma treatment. Use an air atmosphere plasma excitation device to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, set the discharge voltage to 30 kV, the frequency to 50 kHz, and the working distance to 3 cm, and after plasma discharge for 5 minutes, a plasma activation layer is formed on the film surface.

[0027] Step 2: Prepare the precursor solution. Zirconium tetrachloride, trimesic acid, and a mixture of deionized water and glacial acetic acid are sequentially added into a pressure tube, wherein the molar ratio of zirconium tetrachloride to trimesic acid is 5.1:5, and the volume ratio of deionized water and glacial acetic acid is 3:2. Ultrasonicate the mixture for 30 minutes to make it evenly dispersed.

[0028] Step 3: In-situ loading. Through the continuous folding method, the base material forming the surface activation layer is immersed in the precursor solution, the immersion temperature is 25°C, and the immersion time is 5 minutes. Then, it is placed in a 90°C oven to react for 12 hours. After the reaction is completed, it is cooled to room temperature, the membrane is taken out and rinsed three times in water and methanol respectively, and vacuum dried to obtain a composite protective material with MOF808 loaded on the surface.

[0029] The SEM image of the composite protective material obtained in Example 1 is as follows Figure 1 The thickness of the composite protective material is 0.15 mm, the breaking strength is 6.1 ± 1.5 MPa, the liquid-gas protection time for amyl sulfide is 235 min, and the moisture permeability is 1900 g / (m 2 ·24h), the degradation conversion rate of 2-CEES (mustard gas simulant) was 96%.

[0030] Example 2 A plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof, comprising the following steps: Step 1: Plasma treatment. Use a plasma excitation device in an oxygen atmosphere to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, set the discharge voltage to 30 kV, the frequency to 50 kHz, and the working distance to 3 cm, and after plasma discharge for 10 minutes, a plasma activation layer is formed on the film surface.

[0031] Step 2: Prepare the precursor solution. Zirconium tetrachloride, trimesic acid, and a mixture of deionized water and glacial acetic acid are sequentially added into a pressure tube, wherein the molar ratio of zirconium tetrachloride to trimesic acid is 5.1:5, and the volume ratio of deionized water and glacial acetic acid is 3:2. Ultrasonicate the mixture for 30 minutes to make it evenly dispersed.

[0032] Step 3: In-situ loading. Through the continuous folding method, the base material forming the surface activation layer is immersed in the mixture and placed in a 100°C oven to react for 24 hours. After the reaction is completed, it is cooled to room temperature, the membrane is taken out and rinsed three times in water and methanol respectively, and vacuum dried to obtain a composite protective material with MOF808 loaded on the surface.

[0033] The composite protective material obtained in Example 2 has a thickness of 0.15 mm, a breaking strength of 5.1±2.1 MPa, a liquid-gas protection time of 120 min for amyl sulfide, and a moisture permeability of 2200 g / (m 2 ·24h), the degradation conversion rate of 2-CEES (mustard gas simulant) was 95%.

[0034] Example 3 A plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof, comprising the following steps: Step 1: Plasma treatment. Use a plasma excitation device in a nitrogen atmosphere to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, set the discharge voltage to 30 kV, the frequency to 50 kHz, and the working distance to 3 cm, and after plasma discharge for 5 minutes, a plasma activation layer is formed on the film surface.

[0035] Step 2: Prepare the precursor solution. Add zirconium oxychloride octahydrate, trimesic acid, and deionized water to the pressure tube in sequence, stir for 1 hour, and then add trifluoroacetic acid, wherein the molar ratio of zirconium oxychloride octahydrate to trimesic acid is 2.25:1, and the mixed volume ratio of deionized water / trifluoroacetic acid is 2:1. Ultrasonicate the mixture for 30 minutes to make it evenly dispersed. Soak the base material forming the surface activation layer in the mixture, place it in a 120°C oven, and allow the reaction to proceed for 2 hours. After the reaction is completed, cool to room temperature, take out the membrane, rinse it three times in water and methanol respectively, and vacuum dry it to obtain a composite protective material with MOF808 loaded on the surface.

[0036] The composite protective material obtained in Example 3 has a thickness of 0.14 mm, a breaking strength of 5.7±2.1 MPa, a liquid-gas protection time of 274 min for amyl sulfide, and a moisture permeability of 1750 g / (m 2 ·24h), the degradation conversion rate of 2-CEES (mustard gas simulant) was 98%.

[0037] Example 4 A plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof, comprising the following steps: Step 1: Plasma treatment. Use an air atmosphere plasma excitation device to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, set the discharge voltage to 30 kV, the frequency to 50 kHz, and the working distance to 3 cm, and after plasma discharge for 5 minutes, a plasma activation layer is formed on the film surface.

[0038] Step 2: Prepare the precursor solution. Add zirconium tetrachloride and acetone solution to the pressure tube in sequence, ultrasonicate for 10 minutes until completely dissolved, and then add 2-aminoterephthalic acid, wherein the molar ratio of zirconium tetrachloride and 2-aminoterephthalic acid is 1:1. Ultrasonicate the mixture for 30 minutes to make it evenly dispersed. Soak the base material forming the surface activation layer in the mixture, place it in an oven at 85°C, and allow the reaction to proceed for 24 hours. After the reaction is completed, cool to room temperature, take out the membrane, wash it with DMF and anhydrous ethanol 2-3 times respectively, and vacuum dry it to obtain a composite protective material with surface loaded UiO-66-NH2.

[0039] The composite protective material obtained in Example 4 has a thickness of 0.16 mm, a breaking strength of 6.5 ± 0.9 MPa, a liquid-gas protection time of 262 min for amyl sulfide, and a moisture permeability of 2000 g / (m 2 ·24h), the degradation conversion rate of 2-CEES (mustard gas simulant) was 96%.

[0040] Example 5 Based on Example 4, the prepared composite protective material with UiO-66-NH2 loaded on the surface was immersed in a 0.1M NaOH solution for 2 hours, and finally washed by centrifugation with DMF and ethanol to obtain a composite protective material with Zr(OH)4 loaded on the surface.

[0041] The composite protective material obtained in Example 5 has a thickness of 0.15 mm, a breaking strength of 6.6±1.3 MPa, a liquid-gas protection time of 195 min for amyl sulfide, and a moisture permeability of 2232 g / (m 2 ·24h), the degradation conversion rate of 2-CEES (mustard gas simulant) was 94%.

[0042] Comparative Example 1 A plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof, comprising the following steps: Step 1: Plasma treatment. Use an air atmosphere plasma excitation device to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, set the discharge voltage to 15 kV, the frequency to 50 kHz, and the working distance to 3 cm, and after plasma discharge for 5 minutes, a plasma activation layer is formed on the film surface.

[0043] Step 2: Prepare the precursor solution. Zirconium tetrachloride, trimesic acid, and a mixture of deionized water and glacial acetic acid are sequentially added into a pressure tube, wherein the molar ratio of zirconium tetrachloride to trimesic acid is 5.1:5, and the volume ratio of deionized water and glacial acetic acid is 3:2. Ultrasonicate the mixture for 30 minutes to make it evenly dispersed.

[0044] Step 3: In-situ loading. Through the continuous folding method, the base material forming the surface activation layer is immersed in the precursor solution, the immersion temperature is 25°C, and the immersion time is 5 minutes. Then, it is placed in a 90°C oven to react for 12 hours. After the reaction is completed, it is cooled to room temperature, the membrane is taken out and rinsed three times in water and methanol respectively, and vacuum dried to obtain a composite protective material with MOF808 loaded on the surface.

[0045] The MOF in-situ loading effect on the surface of the composite protective material obtained in Comparative Example 1 was not good, and the degradation test results showed that the degradation conversion rate of 2-CEES (mustard gas simulant) was 75%. In this embodiment, the lower voltage may not be able to effectively maintain the formation of plasma, resulting in unstable discharge and affecting the treatment effect. The reduction in discharge voltage may lead to insufficient energy input and fail to achieve the desired treatment depth or effect.

[0046] Comparative Example 2 A plasma-assisted composite protective material for self-degradation of toxic agents and a preparation method thereof, comprising the following steps: Step 1: Plasma treatment. Use an air atmosphere plasma excitation device to modify the surface of the polyvinylidene fluoride quaternary ammonium film. Combine the stage of the glow discharge plasma treatment equipment with the automatic feeding component, set the discharge voltage to 30 kV, the frequency to 50 kHz, and the working distance to 3 cm. After 15 minutes of plasma discharge, a plasma activation layer is formed on the surface of the film.

[0047] Step 2: Prepare the precursor solution. Zirconium tetrachloride, a mixture of deionized water / glacial acetic acid, and trimesic acid are added to the pressure tube in sequence, wherein the molar ratio of zirconium tetrachloride to trimesic acid is 5.1:5, and the mixed volume ratio of deionized water / glacial acetic acid is 3:2. Ultrasonicate the mixture for 30 minutes to make it evenly dispersed.

[0048] Step 3: In-situ loading. Through the continuous folding method, the base material forming the surface activation layer is immersed in the precursor solution, the immersion temperature is 25°C, and the immersion time is 5 minutes. Then, it is placed in a 90°C oven to react for 12 hours. After the reaction is completed, it is cooled to room temperature, the membrane is taken out and rinsed three times in water and methanol respectively, and vacuum dried to obtain a composite protective material with MOF808 loaded on the surface.

[0049] The composite protective material obtained in Comparative Example 1 has only a small amount of MOF loaded on its surface, and the degradation test results show that the degradation conversion rate of 2-CEES (mustard gas simulant) is 26%. In this embodiment, too long a treatment time may cause the surface of the substrate to be irradiated with excessive energy, resulting in thermal damage or physical damage to the material.

[0050] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A plasma-assisted composite protective material for self-degradation of toxic agents, characterized in that: include: The inner layer substrate material is a selective permeable material, including one or more of polyvinylidene fluoride quaternary ammonium membrane, polyvinylidene fluoride sulfonic acid membrane, and sulfonated polyphenylene ether membrane materials; The active components grown in situ on the surface of the substrate material based on plasma treatment have the functions of adsorbing and catalytically degrading toxic agents, including one or more zirconium-based metal organic frameworks and Zr(OH)4.

2. The plasma-assisted self-degradable composite protective material for toxic agents according to claim 1, characterized in that: The zirconium-based metal organic framework is selected from MOF808 or UiO-66-NH2.

3. A plasma-assisted method for preparing a composite protective material for self-degradation of toxic agents, characterized in that: The preparation method steps are as follows: Step 1: plasma treatment, using a plasma excitation device in air, nitrogen or oxygen atmosphere to modify the surface of the substrate material; combining the stage of the glow discharge plasma treatment equipment with the automatic feeding component, setting the discharge voltage, frequency, working distance and other parameters, and forming a plasma activation layer on the film surface after plasma discharge for a period of time; Step 2: prepare a precursor solution and mix it by ultrasonic to make it evenly dispersed; Step 3: In-situ loading: by continuous folding, the substrate material forming the surface activation layer is immersed in the precursor solution, and the temperature is raised to react after immersion; After the reaction is completed, the film is cooled to room temperature, taken out, washed, and vacuum dried to obtain a composite protective material with active components loaded on the surface.

4. The preparation method according to claim 3, characterized in that: In step 1, the discharge voltage is 30-50 kV, the frequency is >40 kHz, the working distance is 3-5 cm, and the discharge time is 5-10 min.

5. The preparation method according to claim 3, characterized in that: In step 2, the precursor solution is selected from a mixture of zirconium oxychloride octahydrate, trimesic acid, glacial acetic acid and deionized water, the molar ratio of zirconium oxychloride octahydrate and trimesic acid is 0.8-3, and the volume ratio of glacial acetic acid and deionized water is 0.2-0.

8.

6. The preparation method according to claim 5, characterized in that: In step 2, the precursor solution can also be a mixture of zirconium oxychloride octahydrate, trimesic acid, trifluoroacetic acid and deionized water, the molar ratio of zirconium oxychloride octahydrate and trimesic acid is 0.8-3, and the volume ratio of trifluoroacetic acid and deionized water is 0.2-0.

8.

7. The preparation method according to claim 6, characterized in that: In step 2, the precursor solution may also be a mixture of zirconium tetrachloride, 2-aminoterephthalic acid and acetone, and the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 0.8 to 1.

2.

8. The preparation method according to claim 7, characterized in that: In step 2, the precursor solution can also be a mixture of zirconium tetrachloride, terephthalic acid, acetic acid and N,N-dimethylformamide, the molar ratio of zirconium tetrachloride and terephthalic acid is 0.2-0.5, and the volume ratio of acetic acid and N,N-dimethylformamide is 0.01-0.

2.

9. The preparation method according to claim 7, characterized in that: In step three, the immersion temperature is 25-30°C, the immersion time is 4-6 minutes, and after being taken out, it is placed at 80°C-140°C for reaction for 12h-24h. In step three, the membrane material is reacted, washed, and vacuum-dried in the precursor solution, and then immersed in a NaOH solution at room temperature for 1-2h, and the mass concentration of the NaOH solution is 0.1-0.5M; finally, it is centrifuged and washed with DMF and ethanol to obtain the final product.

10. A material for degrading dichloroethyl ethyl sulfide, characterized in that: The material is selected from the plasma-assisted self-degradation composite protective material for toxic agents as described in claim 1 or 2 or the plasma-assisted self-degradation composite protective material for toxic agents prepared by the method described in any one of claims 3-9.